Ergonomic risk assessment of surgeon's position during radical prostatectomy: Laparoscopic versus robotic approach - Hayashi, Marcel Calegari; Sarri, Almir J.; Pereira, Pâmella Arielle Sandrin Veitas; Rocha, Mauricio Murce; Zequi, Stenio de Cassio; Machado, Marcos Tobias; Souza, Alessandra Hübner; Magno, Luiz Alexandre Viana; Faria, Eliney Ferreira (Journal of surgical oncology, 2023)
Background and Objectives Radical prostatectomy (RP) is a definitive surgical therapy for localized prostate cancer. Evidence suggests that the poor ergonomics of surgeons during RP may lead to work‐related musculoskeletal disorders and loss of productivity. Since each surgery modality has its physical demands, we compared the ergonomic risk between laparoscopic (LRP) and robotic‐assisted (RARP) radical prostatectomy. Methods The study assessed the posture of 10 urological surgeons during LRP and RARP surgeries with the Rapid Entire Body Assessment (REBA) scale. Results We found that the RARP approach resulted in lower REBA scores over the LRP procedure. Conclusions Robotic surgery improves body posture for the urological surgeon like in other medical specialties. However, the surgeons display harmful postures in both surgeries.